Огляд можливостей для використання технології анагліф у сфері візуалізації - Лозовська, Г. О. (ХНУРЕ, 2025)
The article discusses the history and applications of anaglyph technology. Anaglyph is a stereoscopic imaging technology that uses two color layers and filter glasses. Despite the emergence of new technologies, anaglyph remains popular due to its simplicity, affordability, and versatility across different media. This technology is used in science, education, and modern art.
Keywords: технологія анагліф; візуалізація